2019
DOI: 10.2141/jpsa.0180095
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Tea Tree (<i>Melaleuca alternifolia</i>) Oil Supplementation Improves Growth Performance, Cecal Microflora, Immunity, and Antioxidant Capacity of Partridge Shank Chickens

Abstract: The aim of this study was to investigate the effects of tea tree oil (TTO) supplementation on the growth performance, cecal microflora composition, immunity, and antioxidant status of Partridge Shank chickens. A total of 144 one-day-old chicks were allocated into three treatments with six replicates of eight chicks each and fed with a basal diet supplemented with 0 (Control group), 500, and 1000 mg/kg TTO for 50 days. Compared with the control group, the broilers fed with the basal diet supplemented with 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It has been reported ( Dong et al, 2019 ) that supplement of 150 mg/kg TTO in daily feed improves intestinal mucosal immunity significantly in weaning pigs compared to the use of antibiotics. Similar benefits have been reported in poultry medicine, which revealed that adding TTO in daily feed improves growth performance, cecum microflora, immunity, and antioxidant capacity in Partridge Shank chickens ( Qu et al, 2019 ). However, information regarding how TTO affects intestinal morphology, immunity, and growth performance in Fengyan black bone chickens ( Ayam Cemani ) remains scant.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…It has been reported ( Dong et al, 2019 ) that supplement of 150 mg/kg TTO in daily feed improves intestinal mucosal immunity significantly in weaning pigs compared to the use of antibiotics. Similar benefits have been reported in poultry medicine, which revealed that adding TTO in daily feed improves growth performance, cecum microflora, immunity, and antioxidant capacity in Partridge Shank chickens ( Qu et al, 2019 ). However, information regarding how TTO affects intestinal morphology, immunity, and growth performance in Fengyan black bone chickens ( Ayam Cemani ) remains scant.…”
Section: Introductionsupporting
confidence: 65%
“…The results of this study showed that ADG increased significantly while F/G significantly decreased with supplement of TTO since 14th day of the study. Qu et al (2019) found that TTO supplementation had a significant effect on ADG in Partridge Shank chickens. Therefore, these results indicate that the addition of TTO to the ration can promote broiler growth and increase the feed conversion ratio.…”
Section: Discussionmentioning
confidence: 92%
“…This shows that the addition of TTO does not change the flavor or amino acid content of goats. Studies have claimed that TTO can improve animal growth performance (Abo Ghanima et al, 2021 ; Puvaca et al, 2019 ; Qu et al, 2019 ). In animals, muscle protein turnover (protein synthesis and decomposition) is a critical factor affecting growth performance, but the effect of TTO on protein turnover in muscle tissue is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…shows that the addition of TTO does not change the flavor or amino acid content of goats. Studies have claimed that TTO can improve animal growth performance (AboGhanima et al, 2021;Puvaca et al, 2019;Qu et al, 2019). In animals, muscle protein turnover F I G U R E 2 Schematic diagram for tea tree oil improving intestinal immunity by enhancing amino acid transport in the ileal mucosa of goats.…”
mentioning
confidence: 99%
“…However, few studies have investigated its effects as a dietary supplement for chickens in plateau areas. And Partridge Shank chicken, a native poultry strain in China, not only provide exquisite and nutrient-rich meat for Chinese consumers, but also exhibit strong adaptability and disease resistance compared with commercial broiler strain (Qu et al 2019). It is generally slaughtered at 75 day-old.…”
Section: Introductionmentioning
confidence: 99%